Staff experiences with remote work in a comprehensive cancer center during the COVID-19 pandemic. Issue 28 (1st October 2022) - McChesney, Christopher; Powis, Melanie Lynn; Espin-Garcia, Osvaldo; Morley, Lyndon; Hack, Saidah; Krzyzanowska, Monika K.
Abstract : 41 Background: The COVID-19 pandemic led to the rapid implementation of remote work, but few studies have evaluated the impact on staff and care delivery in healthcare settings. Utilizing a cross-sectional survey, we evaluated the experience of working remotely among clinical staff at the Princess Margaret Cancer Centre, Toronto, Canada. Methods: "Remote work" was defined as any work (tasks, projects, healthcare delivery) performed from home. A Qualtrics survey was disseminated via email three times from June-August 2021 to 1, 168 physicians, nurses, allied health, and administrative staff involved in patient care. The survey evaluated staff perceptions of productivity, efficiency, patient safety, quality, and personal experiences. Results were summarized using descriptive statistics. Associations between respondent demographics and responses on perceived efficiency, desire to work remotely, support and safety/quality were evaluated using multivariable binary logistic regression models. Free-text responses were categorized into facilitators and barriers, and summarized using qualitative descriptive analysis. Results: Most respondents (n = 333; response rate: 28.5%) were female (61.3%) and physicians (23.1%). Few respondents (1.5%) worked remotely more than half the time pre-COVID which increased to 66.6% during COVID-19. Majority reported that remote work positively impacted productivity (61.8%) and efficiency (57.6%) and expressed interest in continuing (79.0%) beyond the pandemic. While most respondents agreed with the switch to remote work (89.2%), few were provided with the necessary equipment (14.1%). Some respondents perceived a negative impact on the safety (13.8%) or quality of care (18.6%) delivered remotely. Across clinical roles, compared to administrative staff, physicians were more likely to report remote work having a negative impact on productivity (OR = 24.04, 95% CI: 2.71-213.00), being dissatisfied with remote work (OR: 8.41, 95% CI: 1.37-51.64), being dissatisfied with training available (OR: 2.70, 95% CI: 0.95-7.67), and disagreed with continuing to utilize remote work beyond the pandemic (OR: 16.61, 95% CI: 1.45-190.14). Improved efficiency, less commuting, and improved work-life balance were perceived as facilitators of remote work. Barriers included a lack of clear role expectations, issues accessing clinical applications and out-of-pocket expenses. Conclusions: Our findings indicate that remote work may be a viable model in hospitals beyond the pandemic. Given the variation in experience and perceptions depending on clinical role, addressing barriers and formal evaluation of the impact of working remotely on productivity, efficiency and quality of care should be considered to inform long-term adoption.